Introduction to the 2018 Research Symposium Forum - Kiran, Swathi (J Speech Lang Hear Res, 2019)
PURPOSE: The purpose of this introduction is to provide an overview of the articles contained within this forum of Journal of Speech, Language, and Hearing Research (JSLHR). Each of these articles is based upon presentations from the Research Symposium at the 2018 annual convention of the American Speech-Language-Hearing Association held in Boston, MA. QUESTION AND ANSWER PANEL: https://doi.org/10.23641/asha.11120825